Psychological Factors Predicting Employability Skills Among National Youth Service Corps (N. Y. S. C.) Members In Kwara State, Nigeria - Kamoru Abidoye TIAMIYU; Olalekan ABUBAKAR ABDULKAREEM; Jamila YUSUF; Habibat Bolanle ABDULKAREEM (Universitas Pendidikan Ganesha, 2025)
Although the National Youth Service Corps (N.Y.S.C.) program is designed to improve the employability of college graduates, many members still exhibit low employability skills and struggle to adapt to the demands of the workforce. This raises questions about the extent to which psychological factors such as self-efficacy, achievement motivation, and emotional intelligence can predict the employability skills of N.Y.S.C. members in Kwara State, Nigeria. The purpose of this study was to analyze and determine the extent to which psychological factors such as self-efficacy, achievement motivation, and emotional intelligence can predict employability skills among N.Y.S.C. members. A correlational research design was adopted, involving 250 participants selected through simple random sampling. Data were collected using three standardized instruments: the Career Adaptability Scale (CAS, r = 0.82), the Self-Efficacy Scale (SES, r = 0.73), and the Employability Skills Scale (ESS, r = 0.59). Pearson Product Moment Correlation and Multiple Regression were used to analyze the data, with hypotheses tested at a significance level of 0.05. The findings revealed a significant positive relationship between career adaptability and employability skills (r = 0.64, p < 0.05), and between self-efficacy and employability skills (r = 0.64, p < 0.05). The combined predictive effect of both factors was significant (Adjusted R² = 0.59, F(2,97) = 71.13, p < 0.05), with career adaptability (β = 0.47) and self-efficacy (β = 0.46) contributing significantly. In conclusion, psychological factors such as self-efficacy, achievement motivation, and emotional intelligence were shown to play an important role in predicting and enhancing employability skills of N.Y.S.C members.